O meio ambiente de trabalho saudável dos magistrados como direito fundamental: implicações da política de metas do Conselho Nacional de Justiça - Silva, Elisete Regina Meneghetti (2015)
The survey was conducted in the Labour Law, which addresses the means balanced work environment as a fundamental right of every worker area. Brings the issue involving the environment, which gains new constitutional garb being erected by the Constitution of 1988 as essential to a healthy quality of life as well, whose duty to preserve his equilibrium, by government and by the community, it appears as a right fundamental of the human person. Show that this social right should be guaranteed with the help of SUS - National Health System to collaborate on environmental protection work, consecrating it as a corollary of the right to health. Points out that, although the issue has been studied and researched, there is almost no doctrine and jurisprudence, authors addressing the imbalance caused in the environment of magistrates' work with the implementation of the Policy Goals of the National Council of Justice and the impacts of this model management in the health of the judges. Demonstrates that the quality of life of magistrates is linked to access to justice. Highlights the work done in an inappropriate environment affects physical and intellectual integrity of the judge, thus compromising the quality of adjudication. Sought to meet the policy goals of the CNJ and analyze its implementation as access to justice, from the perspective of the reasonable duration of the process and the means to guarantee the speed of their processing mechanism. Scientific research sought to answer the following questions: what are the impacts of the Policy Goals of CNJ the quality of life of the magistrates? What are the implications and consequences of this policy on physical and psychological health of the judges? Addressed the following objectives: to study the implications of the goals assigned by CNJ the working environment for judges; analyze the impacts and consequences of the goals of the CNJ environmental balance of the work of judges. Used the dialectical method based on research through a literature review of issues involving this work. Described the contemporary design of the working environment as a fundamental right, identified traces of fundamentality of this artificial environment, their holders, notably the magistrate, from the characteristics of its operations in the Brazilian system. Focused on the fundamental right of access to justice in the shed sustained by Mauro Cappelletti and Bryant Garth. The role of the magistrate like as guarantor social actor's effective access to justice. Described the policy goals of the CNJ, trying to identify its constitutional role and institutional powers in the Brazilian legal context, their duties and legitimacy to implement the goals the Judiciary. Analyzes the impacts of this management in the work environment of the magistrates, in their healthy quality of life and delivery of judicial services. The survey revealed that although the policy goals of the CNJ has advanced in seeking access to justice, in response to the clamor for urgent reforms were undertaken under the Judiciary aiming mainly to ensure the implementation vanished the person of the judge. Suggested urgency in the execution of projects that are underway, under the ownership of the CNJ, designed to assess the health of the judges and secure a balanced working environment for judges of law, which is due to the pressing need to humanize the work and prioritize the human person in the exercise of the judiciary.